Autologous Islet Transplantation in Patients Requiring Pancreatectomy: A Broader Spectrum of Indications Beyond Chronic Pancreatitis. Issue 6 (1st March 2016) - Balzano, G.; Maffi, P.; Nano, R.; Mercalli, A.; Melzi, R.; Aleotti, F.; Zerbi, A.; De Cobelli, F.; Gavazzi, F.; Magistretti, P.; Scavini, M.; Peccatori, J.; et al.
Abstract : Islet autotransplantation (IAT) is usually performed in patients undergoing pancreatic surgery for chronic pancreatitis. In the present series, IAT was offered also to patients undergoing pancreatic surgery for both nonmalignant and malignant diseases, having either completion pancreatectomy as treatment for severe pancreatic fistulas (n = 21) or extensive distal pancreatectomy for neoplasms of the pancreatic neck (n = 19) or pancreatoduodenectomy because of the high risk of pancreatic fistula (n = 32). Fifty‐eight of 72 patients who were eligible to this broader spectrum of indication actually received IAT. There was no evidence of a higher‐than‐expected rate of major complications for pancreatectomy. Forty‐five patients receiving IAT were still alive at the time of the last scheduled follow‐up (1375 ± 365 days). Eighteen (95%) of 19 and 11 (28%) of 39 patients reached insulin independence after partial or total pancreatectomy, respectively. The metabolic results were dependent on the transplanted islet mass. Thirty‐one of 58 patients had malignant diseases of the pancreas or periampullary region, and only three patients developed ex novo liver metastases after IAT (median follow‐up 914 ± 382 days). Our data demonstrate the feasibility, efficacy, and safety of IAT for a broader spectrum of clinical indications beyond chronic pancreatitis. Abstract : The authors propose extending clinical indications for islet autotransplantation in patients undergoing pancreatic surgery for both nonmalignant and malignant pancreas diseases, including complete pancreatectomy because of the high risk of anastomotic leakage after pancreaticoduodenectomy.